2020
DOI: 10.2147/ndt.s278471
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of Prevention Measures and Information About Coronavirus in Romanian Male Patients with Severe Mental Illness and Severe Alcohol Use Disorder</p>

Abstract: Purpose: Patients with severe mental illness (SMI) and alcohol use disorder (AUD) are at higher risk for contracting coronavirus-19 (COVID-19) and for poor outcomes of COVID-19 infection. One reason for this could be the lack of knowledge regarding preventive measures against COVID-19 and the inability of the psychiatric patients to discern misinformation from facts. Patients and Methods: The study design was cross-sectional. We applied one questionnaire that evaluated knowledge of prevention measures and info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The last but not the least is the reverse analysis – how alcohol use disorder may influence the way of dealing with the pandemic from the personal safety perspective. The results of a cross-sectional survey, performed in Romania, on 115 male patients and 57 controls, showed that patients with severe mental illness (SMI) and alcohol use disorder (AUD) are at higher risk for contracting COVID-19 and for poor outcomes of COVID-19 infection, one reason being the lack of knowledge regarding preventive measures against COVID-19 and the inability to discern misinformation from facts [ 82 ].…”
Section: Covid-19 Pandemic Lockdown and Alcohol Consumption: Connectmentioning
confidence: 99%
“…The last but not the least is the reverse analysis – how alcohol use disorder may influence the way of dealing with the pandemic from the personal safety perspective. The results of a cross-sectional survey, performed in Romania, on 115 male patients and 57 controls, showed that patients with severe mental illness (SMI) and alcohol use disorder (AUD) are at higher risk for contracting COVID-19 and for poor outcomes of COVID-19 infection, one reason being the lack of knowledge regarding preventive measures against COVID-19 and the inability to discern misinformation from facts [ 82 ].…”
Section: Covid-19 Pandemic Lockdown and Alcohol Consumption: Connectmentioning
confidence: 99%
“…Most individuals with SMI had a positive stance regarding measures for preventing COVID-19[ 50 , 51 ], which was related to marriage and a higher level of education[ 51 ]. However, they were on average not as knowledgeable about COVID-19 and measures of prevention as HC[ 52 , 53 ]. This reduced knowledge was associated with a low socioeconomic status, little education, and insufficient social support[ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…An increased belief in pandemic-related news was found to be associated with both increased[ 55 ] and decreased[ 50 ] fear in individuals with SMI, which may be related to the nature of information. Regardless of whether these individuals were more or less[ 53 ] informed about COVID-19 and its prevention than HC, they were generally more fearful and worried about the pandemic[ 58 , 76 , 77 ]. This is concerning if it is related to less prevention behavior[ 50 ], because individuals with SMI show more vulnerability to infection with COVID-19 than HC[ 94 , 95 ] and should therefore practice strict measures of prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown differences in patients with mental disorders with regard to the COVID-19 pandemic. In a study that assessed the level of general knowledge regarding the COVID-19 pandemic and how to prevent it, patients with a severe mental disorder scored 19.2% lower than the control group on rating scales (Matei et al, 2020 ). On the other hand, compared to the control group without mental disorders, 85% of patients were able to make better use of their free time, with relaxation and meditation activities (González-Blanco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%